Corticosteroid use in neurocysticercosis. (August 2011) - Nash, Theodore E; Mahanty, Siddhartha; Garcia, Hector H
The cystic larvae of Taenia solium commonly infect the human nervous system, resulting in neurocysticercosis, a major contributor to seizure disorders in most of the world. Inflammation around the parasites is a hallmark of neurocysticercosis pathophysiology. Although mechanisms regulating this inflammation are poorly understood, anti-inflammatory drugs, particularly corticosteroids, have been long used alone or with anthelmintics to manage disease and limit neurological complications and perhaps damage to neural tissues. Only scarce controlled data exist to determine when and what type of corticosteroids and the treatment regime to use. This article revisits the mechanisms of action, rationale, evidence of benefit, safety and problems of corticosteroids in the context of neurocysticercosis, as well as alternative anti-inflammatory strategies to limit the damage caused by inflammation in the CNS.